The Wine Quality of Merlot Relies in Irrigation Supplementation and Spotlights Sustainable Production Constraints in Mediterranean-Type Ecosystems - Camila Ribalta-Pizarro; Paula Muñoz; Sergi Munné-Bosch (Australian Journal of Grape and Wine Research)
Background and Aims. The Mediterranean climate has been traditionally favorable for winemaking and irrigation practice has been historically avoided and even forbidden, but current productive scenarios are suffering radical changes because of global warming. Therefore, seeking sustainable approaches to improve water availability is key to obtaining high-quality wines and maintain its style, without affecting yields. Methods and Results. Here, we aim to evaluate the effect of irrigation in Merlot vineyards, on grapes production and quality, and also on wine acceptability. Field-grown grapevines from cv. “Merlot” were subjected to two different water supplies in the field: (i) nonirrigated plants and (ii) irrigated plants with 50% of crop evapotranspiration, from veraison to commercial harvest. We assessed water stress markers such as leaf relative water content, leaf hydration, and the maximum efficiency of photosystem II photochemistry, as well as grape and wine quality parameters, wine acceptability, and preference with a panel composed of 100 participants. Furthermore, we performed a systematic review study for comparison, including 9 published reports on Merlot grapevines subjected to different water regimes, oriented to improve irrigation decisions, yield, and/or quality. Results showed that half water supply on grapevines not only induced an increase in the volume and weight of grapes, but the resulting wines had a lower total acidity and showed more desirable chromatic properties, increasing colour intensity and hue, and decreasing brightness. Sensory analysis revealed that 63% of the untrained panel preferred wines from the irrigation treatment. Integrating previously reported data, it is observed that water scarcity is favorable for quality only when compared with fully irrigated vineyards. Conclusions. It is concluded that a half irrigation can be enough to improve grape quality under Mediterranean conditions, without affecting yield components and enhancing sensory characteristics that can improve wine acceptance by consumers. Water management approaches to sustainably provide this extra amount of water to irrigate field-grown grapevines under the current context of climate change are discussed. Significance of the Study. The present study’s findings provide valuable information regarding water management in Mediterranean vineyards and its effects on the suitability of these areas to maintain high-quality wine production.